BANGKITKAN UMKM CINCAU DENGAN DIGITAL BRANDING PRODUK - Musrifah, Ai; Dita, Dita; Yasir, Muhamad; Hendy, Hendy (JE (Journal of Empowerment), 2023)
ABSTRAK Persepsi positif konsumen terhadap suatu produk dapat dipengaruhi oleh branding, karena konsumen dapat mengenali nama, desain, atau merek suatu produk melalui brand tersebut, sehingga produk kita dapat membedakan dengan produk pesaing. Pemasaran, merek, desain, dan pengemasan produk UMKM adalah masalah yang sama. Berdasarkan analisis masalah ini, tujuan utama dari pengabdian kepada masyarakat ini adalah untuk meningkatkan bisnis UMKM minuman Cincau dengan menggunakan branding kemasan digital untuk meningkatkan daya saing dan membuat. Diharapkan dengan membangun branding untuk produk cincau ini, konsumen dari berbagai daerah dapat membeli dan membagikannya kepada orang-orang di seluruh dunia di tempat pemasaran minuman cincau di Desa Haurwangi Kecamatan Haurwangi Kabupaten Cianjur. ABSTRACTConsumers' positive perception of a product can be influenced by branding, because through a brand consumers can recognize the name, design or brand of a product so they can differentiate our product from competitors. The same problems found with MSME products are product marketing, branding, design and packaging of MSME products. Based on the analysis of these problems, the aim of this community service is to improve the MSME business of grass jelly drinks by creating a digital branding for grass jelly product packaging that can increase competitiveness in the market and make. By creating a branding for grass jelly products, the author expected that in the future this grass jelly product will not only be marketed only in the area around the village, but can be purchased and made into souvenirs by consumers from various regions who stop by at the marketing location for grass jelly drinks which is located in Haurwangi Village, Haurwangi District, Cianjur Regency.